Menguatkan Pendekatan Tradisi Sorongan dan Bandongan: Studi Kasus pada Pembelajaran Bahasa Arab (Kitab Kuning) di Pondok Pesantren Madura - Mohammad Jailani; Yoyo; Djamaluddin Perawironegoro (Shaut al Arabiyyah, 2022)
The development of technology and information, some educators no longer develop traditional learning. This affected Islamic boarding schools in Madura, some students still could not read the yellow book. Meanwhile, ustadz and kyai have not been creative in developing the yellow book learning. This study aims to analyze the learning of Arabic (Kitab kuning with the sorongan and bandongan traditions approach. The setting of this research is the Babul Ulum Islamic Boarding School in Pamekasan. The subjects of this research consist of ustadz, kiyai, and students. This research is qualitative research based on case studies. Data were collected using interview, observation, and documentation techniques. Data analysis was strengthened by the theory of Miles and Huberman. Namely reduction, display, presentation, and verification of data. The results of the study found that the sorongan and bandongan approaches affected students' learning outcomes 75% of students' learning progress increased significantly. The sorongan and bandongan approaches are still preserved in Madura as a pesantren education culture that leads to the traditional model. Although kiyai and ustadz continue to improve their ability to implement the yellow book material.